THE STATE AND PERSPECTIVES OF THE PENSION AND DISABILITY INSURANCE SYSTEM IN THE REPUBLIC OF SERBIA - ObradoviC, Goran (Ревија за социјална политика/Journal of Social Policy, 2015)
The paper deals with the current state of the system of pension and disability insurance in the Republic of Serbia and the possible directions of change. The author analyses the causes of an extremely poor status of the pension and disability insurance system, based on current financing and intergenerational solidarity. The disadvantages of this system, in addition to its indisputable advantages, are also pronounced in other countries that apply it. However, in countries such as Serbia, there are factors that further complicate its sustainability, such as poor demographic situation, high unemployment rate, and the like. In this context, the text provides a brief overview of the measures taken to date, with the analysis of their short-term and long-term effects, Finally, the author gives a personal view of the direction of development of the pension and disability insurance system in the Republic of Serbia.